2018
DOI: 10.1016/j.prevetmed.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Associations between a decreased veterinary antimicrobial use and resistance in commensal Escherichia coli from Belgian livestock species (2011–2015)

Abstract: In this study the possible association between antibiotic use and resistance was explored, focusing on commensal Escherichia coli from livestock (veal calves, young beef cattle, pigs and broiler chickens) in Belgium between 2011 and 2015. A continuous decreasing trend in antibiotic use was observed for all classes, except for the phenicols. Antibiotic resistance of commensal E. coli significantly decreased for several of the tested antibiotics in all livestock species. A more rapidly reverted resistance was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 19 publications
2
46
0
Order By: Relevance
“…However, this is still in huge contrast to veal calves in Denmark, where 85.4% of total AMU is given parenterally (Fertner et al, 2016). Both the reduction in total AMU, as increased use of injectable antimicrobials, might have contributed to the observed reduction of AMR in indicator bacteria from veal calves as shown recently in the Belgian monitoring program (Chantziaras et al, 2014;Callens et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, this is still in huge contrast to veal calves in Denmark, where 85.4% of total AMU is given parenterally (Fertner et al, 2016). Both the reduction in total AMU, as increased use of injectable antimicrobials, might have contributed to the observed reduction of AMR in indicator bacteria from veal calves as shown recently in the Belgian monitoring program (Chantziaras et al, 2014;Callens et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that the veal sector in Belgium has reached the same plateau phase as observed in the Netherlands and motivation to further reduce might no longer be present (SDA, 2017). Also, the decrease of AMR in Escherichia coli from veal calves stagnated (Callens et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This association was also shown for livestock animals, which has a high impact on consumer protection due to the cross-linking of animal and human bacterial reservoirs [5]. Epidemiological studies revealed either an increase in antimicrobial resistance in populations treated more often with antibiotics [6,7], or a beneficial effect on resistance levels after the introduction of national antimicrobial usage (AMU) reduction campaigns [8]. Under defined experimental conditions, the effect of a selective pressure by antimicrobial usage on the frequency of phenotypically resistant bacteria in swine [9] or the total resistome of bacterial populations [10] was proven.…”
Section: Introductionmentioning
confidence: 89%
“…Antimicrobial resistance (AMR) in zoonotic pathogens adds to this risk [12][13][14][15] because infections with antimicrobial resistant bacteria are more difficult to treat, and result in higher morbidity and mortality [16,17]. Inappropriate antimicrobial use has been shown to be one of the main causes for the development of AMR in commensal and pathogenic bacteria of poultry [17,18]. Exposure to an individual antimicrobial may cause the bacteria to develop resistance to multiple antimicrobials if resistance genes are located on mobile genetic elements [19].…”
Section: Introductionmentioning
confidence: 99%